Design of a Logistics and Safety Plan to Reduce Costs in a Trading MYPE, Trujillo 2022 (LACCEI, 2024)
The objective of this investigation was to determine to what extent the logistics and security plan influences the costs of a commercial MYPE in Trujillo. Likewise, the methodology was of a descriptive-propositive type with a quantitative approach and cross-sectional design. In the diagnosis, it was determined that the logistics and security costs amounted to S/ 66,286, for which an improvement plan was designed according to ABC theory, MRP, EOQ, Monte Carlo simulation and IPERC. In this way, costs were reduced by 74.20%, which represented an amount of S/ 49,184. The economic evaluation was important to make the decision to invest in the improvement plan, obtaining a positive NPV of S/. 8,558, an IRR of 25.63% and a B/C of 1.24 that demonstrate its profitability for the company. It was concluded that the industrial engineering tools used were relevant to reduce costs.